Bio-inspired routing for heterogeneous Unmanned Aircraft Systems (UAS) swarm networking. (October 2021) - Wang, Jian; Liu, Yongxin; Niu, Shuteng; Song, Houbing
Abstract: In this paper, we propose a bio-inspired routing for heterogeneous Unmanned Aircraft Systems (UAS) swarm networking. Inspired by the biological cell paradigm, each UAS swarm has the principal characteristics of cell wall building. Within connection range, the heterogeneous UAS swarm can construct a cell wall for cooperation and collaborations. The evaluation shows that the bio-inspired routing can improve the efficiency, flexibility, and robustness of the heterogeneous UAS swarm networking on a large scale. As the amount of UAS swarm increases, the cell wall construction keeps stable which outperforms the conventional gateway UAS approaches. With cell wall, the heterogeneous UAS swarm networking can achieve high volume throughput and reliable connections. The cell wall approach is decentralized and elastic to the dynamic of UAS swarm networking, and has a great potential to assist the deployment of UAS swarm networking under a variable and scaling environment.